Depressive disorders in women of climacteric age (review of foreign literature for 2012–2016) - N. A. Bokhan; E. V. Lukiyanova; G. G. Simutkin (Бюллетень сибирской медицины, 2018)
Objective: to systematically review foreign literature and interpret results of the review. Tasks: to review foreign papers where factors are considered which provoke development of depression: hormonal, psychological, social as well as neuromediators, hormonal and immune disturbances in depressive disorders in women with physiological climacteric and climacteric syndrome; issues of differential diagnostics of depressions, psychopharmaco- and psychotherapy with subsequent evaluation of clinical efficiency; personality profile of pateints with affective psychopathology.Methods of search: by keywords in Web of Science Core Collection database across foreign journals (2012– 2016). Criteria of inclusion of papers in the review are determined by themes of studies: 1) women of climacteric age; 2) presence of depression or depressive symptoms; 3) presence of climacteric disturbances. In the abstract-bibliographic and scientometric database Web of Science Core Collection 70 bibliographic sources are selected across foreign journals between 2012 and 2016, including journals with high Impact Factor. Studies included in the review are performed at the university clinics, specialized centers. Clinical and sociodemographic characteristics of female patients meet the criterion of compatibility. Most discussed papers are devoted to study of clinical and social-psychological factors of development of climacteric depression. In a number of papers the efficiency of antidepressant therapy, alternative methods and supplementary therapy in women with depressive disorders, climacteric disturbances and co-occurring physical diseases is shown. Most works are performed with involvement of questionnaires (sociodemographic data, anamnesis) and international clinical scales. The main results of the discussed papers are outlined in thematic rubrics.Conclusion. The European and American papers are used in this review more frequently; studies from Asian countries are used more seldom. Reviewed foreign publications reflect worldwide trend to increase of climacteric depression (CD) in the female population with presence in the anamnesis of adolescent (psychoendocrine alteration) and postpartum depression, premenstrual syndrome. Low timely diagnostics of depressions, high incidence rate of somaticized CD are noted. In the structure of climacteric syndrome the psychoemotional disturbances predominate above neurovegetative and metabolic-endocrine or are combined with vegetative dysfunction. The participation in formation of CD (with predominance of mild/moderate severity) of neurohormonal, genetic, biochemical, social-environmental, psychological factors is shown. In the reviewed sources low mood, loss of previous priorities, decrease of productivity and concentration of attention, position of being unprotected, dependence, lack of confidence, self-humiliation, repentance, unbelief in future, insomnias, hypo-/hyperrexia with change of body mass are described in CD but there are no publications on suicidal ideation. It is indicated that CD can flow with hysteric- and nosophobic, somatohypochondriac and asthenohypochondriac component. The authors consider that somatization as an experience of climacteric stress leads to somaticized CD with accent on physical symptoms and repression of depression and anxiety although an association of specific somatic nosologies with symptoms of CD is not described. The association of CD with social-environmental factors (gender, education, profession, social position, financial wealth) is discussed, achievement of the woman is considered as a actor of reduction of CD risk. The authors are highly interested in search for genetic markers (heredity, suicides in relatives), impairment of neuromediator exchange (neurotransmitters serotonin, dopamine, adrenaline, and noradrenaline), neuromorphologic alterations in brain sensorimotor cortex (motor function, attention, perception, memory, and emotional-motivational response), hormonal disturbances (neuroendocrine and metabolic) and psychoneuroimmunological patterns of association with CD. Psychopharmacotherapy in CD is constructed with account for depressive symptoms (antidepressants of activating/sedative action in long-term maintenance regime), background and co-occurring diseases (adequate and pathogenetic and immunotherapy) with involvement in case of absence of contraindications of substitutive hormonotherapy (estrogen, progesterone). Beyond conventional schemes of the therapy the alternative therapy of CD (acupuncture, yoga, phytoestrogen collections, and food additives) is discussed. For heightening the efficiency and safety of the therapy of CD the training in detection of CD signs both for female patients and nurses, psychologists, social workers is proposed.